If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9=7(1-7x)-4(4-8x)
We move all terms to the left:
-9-(7(1-7x)-4(4-8x))=0
We add all the numbers together, and all the variables
-(7(-7x+1)-4(-8x+4))-9=0
We calculate terms in parentheses: -(7(-7x+1)-4(-8x+4)), so:We get rid of parentheses
7(-7x+1)-4(-8x+4)
We multiply parentheses
-49x+32x+7-16
We add all the numbers together, and all the variables
-17x-9
Back to the equation:
-(-17x-9)
17x+9-9=0
We add all the numbers together, and all the variables
17x=0
x=0/17
x=0
| 84b=7 | | 12+15d−17d=–16−4d | | 180=7x-1+6x-1 | | -4(k-11)=-16 | | 140-u=290 | | 0.6x+0.8(40-x)=29.6 | | 1x+7=4x+9 | | 145+(x+6)=180 | | 4x-7+x-22=120 | | 0=1-2y+14y | | 3(2x-1)=2(2x+5 | | r+35/10=9 | | 21/4b+3/8(b-1)=241/8 | | 16g=560 | | 477=x/2(3x-1) | | 3-8=m | | (q)/(3)=31 | | m-1.79=81 | | -20=14w+2w | | 5=-5+k/2 | | 8c+9=73 | | -24=-2d | | 10p+4=34 | | 5=-5k/2 | | -0.4a+194.91=-18.69+11.6a | | 10=-5+a | | 2(v+1)+7=3(v+2)+2v | | 5(1+3k)=10(7+8k | | 9x=5x+5 | | A=4x,B=3x+12,C=x+8 | | 5x-26=3x+24 | | 0=1-2x+14x |